Effect of the charm quark mass on the BFKL γ*γ* total cross section at LEP - Bartels, Jochen; Ewerz, Carlo; Staritzbichler, René (Physics letters, 2000)
We perform a numerical study of various improvements of the LO BFKL prediction for the γ∗γ∗ total cross section in the kinematical region of the L3 detector at LEP. In particular, we study the effects of a massive charm quark and of different photon polarizations. The variation of the BFKL prediction under changes of αs is investigated.